Scratching the Surface: Exploring Women's Roles in Artisanal and Small Scale Mining in Zimbabwe - Munyaradzi A. Dzvimbo; Colleen Ncube; Monica Monga (Budapest International Research and Critics University, 2019)
Artisanal mining communities around the world are diverse, dynamic and distinct in nature they vary from culture-to-culture, region-to-region and mine-to-mine, and change over the course of time.Women within these communities are also heterogeneous and unique; however, they tend to be engaged in specific roles throughout the world.A qualitative approach in form of a descriptive survey research design was adopted, in which purposive systematic sampling was used and qualitative data was generated. Semi-structured questionnaires were used to collect data from predominantly mining towns Kadoma, Kwekwe and Shurugwi as well surrounding areas.The sample size was compelled by the different mining areas which are a considerable distance from each other with sparsely distributed population. The focus of data collection was on women’s responsibilities in mineral processing activities range from crushing, grinding, sieving, washing and panning, to amalgamation and amalgam decomposition in the case of gold mining.Typically, women are labourers (e.g. panners, ore carriers and processors), providers of goods and services (for instance cooks, shopkeepers) and are often solely responsible for domestic chores. The total number of artisanal miners for the three mining towns was 1500 and a sample of 10% (150 miners) of the three towns, with each town having 50 was sampled. The artisanal miners taken to be part of the population sample were systematic selected till the last person. The composition of the miners was made up 41% of the females while the remaining 59% were male respondents.